Pengaruh Balestra Terhadap Hasil Serangan dalam Olahraga Anggar Jenis Senjata Floret - Puji Astuti; Krisno Giovanni (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study aimed to analyze the effect of balestra technique training on attack performance in foil fencing among beginner athletes in Purwakarta Regency. An experimental method with a one group pretest posttest design was employed, involving eight novice fencers selected through purposive sampling. The Kuhadja Fencing Test (validity = 0.80; reliability = 0.81) was used for data collection. Training was conducted over six weeks (16 sessions). Data were analyzed using descriptive statistics, Liliefors normality test, homogeneity test, and paired t-test. Results showed a mean score increase from 53 to 62, but it was statistically non significant (t = 2.37 < t-critical = 3.18; α = 0.05), likely due to small sample size and limited training duration. Nevertheless, findings suggest balestra holds potential for further development with more rigorous methodology.